Mechanical Weakness of the Nankai Accretionary Prism: Insights From Vp Measurements of Drill Cuttings. (13th May 2021) - Kitamura, M.; Hirose, T.; Lei, X.
Abstract: The relationship between P ‐wave velocity ( V p ) and unconfined compressive strength ( C 0 ) can be used to estimate in situ rock strength and stresses at depth in subduction zones. However, few reliable data on the V p ‐ C 0 relationship in deep accretionary prism sediments are available. Here, we determined the V p ‐ C 0 relationship down to ∼3.2 km in the Nankai accretionary prism from V p measurements and indentation tests of drill cuttings retrieved from International Ocean Discovery Program Site C0002. In our results, the Nankai accretionary prism sediments tended to be weaker compared with estimates obtained by using other empirically determined V p ‐ C 0 relationships. We also examined the relationship between V p and porosity in the accretionary prism. The V p ‐porosity relationship obtained by using only data of Nankai accretionary prism sediments showed that V p generally increased with decreasing porosity; this result is consistent with published V p ‐porosity relationships for Nankai Trough sediments. The empirical relationships derived in this study should improve estimates of stress state, pore pressure, and fault strength in the Nankai accretionary prism. Plain Language Summary: Stress conditions in a subduction zone must be known to understand how earthquakes in the zone are generated. To estimate stresses deep underground, the relationship between sonic ( P ‐) wave velocity and rock strength can be used. We thus measured P ‐wave velocity and rock strength of small rocks and sediment chips, called drill cuttings, collected as deep as ∼3.2 km below the seafloor during a scientific ocean drilling project from a geological formation in the Nankai Trough called the Nankai accretionary prism. We then determined the relationship between P ‐wave velocity and rock strength in the accretionary prism sediments. We found that the deep Nankai accretionary prism sediments were weaker than had been previously estimated. Our empirically derived relationship should contribute to improved estimation of stresses in the Nankai accretionary prism. Key Points: The P ‐wave velocity and strength of Nankai accretionary prism sediments were estimated from drill cuttings The velocity‐porosity relationship showed that estimated in situ velocity gradually increased as estimated in situ porosity decreased The relationship between velocity and strength suggests that Nankai accretionary prism sediments are weaker than previously thought